Role of agile leadership in managing inter-role conflicts for a satisfying job and life during COVID-19 in a VUCA world - Aftab, Saima; Khalid, Komal; Waheed, Ajmal; Aftab, Asma; Adnan, Aisha (Frontiers in Psychology, 2022)
This study investigated how agile leadership played its role in managing inter-role conflicts during the chaotic period of the Covid-19 pandemic. The Covid-19 pandemic was much more than the survival of the fittest and coming out of it alive. Organizations were under immense pressure to resume their normal operations in not-so-normal situations. This period of turmoil and agony brought a broad array of inter-role conflicts, which posed challenges for leaders to manage them effectively. The satisfaction at job and satisfaction in life were the two most important endeavors for the employees to fight. This study explores how leadership agility helped employees manage their work-family and family-work conflicts, consequently impacting life satisfaction and job satisfaction simultaneously. Moreover, role ambiguity, role conflict, and role overload are important intervening role stress factors that impact inter-role conflict management. So, role stress is a moderating factor in the direct relationship between agile leadership and inter-role conflict. This is a two-phased time lag study with a quantitative design for data collection. The first phase of data collection comprises of analyzing the impact of agile leadership on inter-role conflict management, keeping in view the intervening impact of role stress. The second data collection phase examines how inter-role conflicts impacted life satisfaction and job satisfaction during Covid-19. The data were collected from faculty working in higher education institutions in Pakistan, as the education industry was the second major sector that was affected because of Covid -19 after the health care industry. This research found that agile leadership plays a significant role in determining job satisfaction and life satisfaction. Agile leadership during the Covid-19 pandemic helped to manage work-family and family-work conflicts and reduce role stress. Future researchers might include marital satisfaction, as the inter-role conflicts highly impacted marital satisfaction and resultant imbalances among dual-earning couples. Comparative studies in this regard, explaining how dual-earning couples managed to sustain marital health and the role of leadership in developed and developing countries would be enlightening.